2019
DOI: 10.1136/bmjhci-2019-100075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of voice assistants’ responses to consumer health questions about vaccines: an exploratory comparison of Alexa, Google Assistant and Siri

Abstract: ObjectiveTo assess the quality and accuracy of the voice assistants (VAs), Amazon Alexa, Siri and Google Assistant, in answering consumer health questions about vaccine safety and use.MethodsResponses of each VA to 54 questions related to vaccination were scored using a rubric designed to assess the accuracy of each answer provided through audio output and the quality of the source supporting each answer.ResultsOut of a total of 6 possible points, Siri averaged 5.16 points, Google Assistant averaged 5.10 point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 16 publications
(29 reference statements)
8
68
0
1
Order By: Relevance
“…The rubric used was adapted from 3 studies on voice assistants in healthcare [5,6,8] and the DISCERN [30] and HONcode [31,32] quality evaluation tools (Figure 1). The point system was adapted from Alagha and Helbing [6]. The rubric evaluated 5 parameters: relevance, reliability, accuracy, comprehensiveness, and user-friendliness of information provided.…”
Section: Evaluation Rubricmentioning
confidence: 99%
See 1 more Smart Citation
“…The rubric used was adapted from 3 studies on voice assistants in healthcare [5,6,8] and the DISCERN [30] and HONcode [31,32] quality evaluation tools (Figure 1). The point system was adapted from Alagha and Helbing [6]. The rubric evaluated 5 parameters: relevance, reliability, accuracy, comprehensiveness, and user-friendliness of information provided.…”
Section: Evaluation Rubricmentioning
confidence: 99%
“…Another study by Boyd and Wilson found that Google internet searches and Google Assistant fared better than Siri for smoking cessation information, but there was room for improvement for all three voice assistants in sourcing expert content [5]. Alagha and Helbing found that Google Assistant and Siri understood consumer queries about vaccine safety and use better and provided more reliable sources than Alexa [6]. In contrast, Miner et al reported that Siri, Cortana, Google Now and S Voice were inconsistent and incomplete in their responses to queries regarding mental health, interpersonal violence and physical health [7].…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent conversational agents and virtual assistants have been used and tested for responding to health information seeking activities [8][9][10][11][12] . Recent efforts have expanded their utilities in health assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, 27% of all web searches used Google Assistant [ 2 ], and the adoption of VA-enabled speakers (eg, Amazon Echo) is increasing, with an estimated $3.5 billion in spending in the United States by 2021 [ 3 ]. In the last 4 years, VA as a digital health tool has been evaluated for information seeking regarding a healthy lifestyle [ 4 ], addiction [ 5 ], vaccination [ 6 ], mental health, and interpersonal violence [ 7 ]. Mental health stands out as a prime candidate for VA-based digital health intervention to fulfill technology’s promise to provide adaptive and personalized care [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%